Eradication of HCV in Renal Transplant Recipients and Its Effects on Quality of Life - Sabbatini, Massimo (Biomed Res Int, 2018)
BACKGROUND: The use of direct antiviral agents (DAA) has radically modified the course of HCV hepatitis in renal patients. Aim of this study was to assess the effects of HCV eradication on quality of life (QOL) in renal transplant recipients (RTR), measured by CLDQ and SF-36. METHODS: Sixteen RTR with well preserved GFR (mean: 60.3±19.3 ml/min) and chronic HCV infection with moderate liver stiffness (9.3±1.7 kPa) were given a sofosbuvir-based regimen for 12 weeks and had a 1 year follow-up. RESULTS: At end of treatment (EOT) a complete viral clearance was observed in all the patients, with normalization of most laboratory data and a consistent reduction in liver stiffness. All these parameters remained stable after 1 year, as well as renal function and proteinuria. Questionnaire data showed consistent amelioration in different “emotional” domains at EOT, which persisted after 1 year and were associated with a globally improved QOL, although there was no change in most of the “physical” domains in both questionnaires. One patient under ribavirin developed an acute anemia and withdrew from the study, but no further adverse episode was observed throughout the study. CONCLUSIONS: Our data, while confirming the efficacy of oral DAA, show that HCV infection represents a heavy psychological burden in renal transplant recipients, greatly alleviated by viral eradication, which determines a significant improvement in QOL that represents an important outcome in management of all transplant recipients. This trial is registered with ISRCTN97560076.